A surgical orthotopic approach for studying the invasive progression of human bladder cancer - Lorenzatti Hiles, Guadalupe; Cates, Angelica L.; El-Sawy, Layla; Day, Kathleen C.; Broses, Luke J.; Han, Amy L.; Briggs, Hannah L.; Emamdjomeh, Amir; Chou, Andrew; Abel, Ethan V.; Liebert, Monica; Palmbos, Phillip L.; et al. (Nature protocols, 2019)
The invasion of bladder cancer into the sub-urothelial muscle and vasculature are key determinants leading to lethal metastatic progression. However, the molecular basis is poorly understood, partly because of the lack of uncomplicated and reliable models that recapitulate the biology of locally invasive disease. We developed a surgical grafting technique, characterized by a simple, rapid, reproducible and high-efficiency approach, to recapitulate the pathobiological events of human bladder cancer invasion in mice. This technique consists of a small laparotomy and direct implantation of human cancer cells into the bladder lumen. Unlike other protocols, it does not require debriding of the urothelial lining, injection into the bladder wall, specialized imaging equipment, bladder catheterization or costly surgical equipment. With minimal practice, the procedure can be executed in <10 min. Tumors develop with a high take rate, and most cell lines exhibit local invasion within 4 weeks of implantation. A small laparotomy is carried out, and human cancer cells are implanted into the mouse bladder lumen. This reproduces the pathobiological events of human bladder cancer invasion in mice.